Strawberry vein banding virus--definitive member of the genus Caulimovirus - Petrzik, K; Benes, V; Mráz, I; Honetslegrová-Fránová, J; Ansorge, W; Spak, J (Virus genes, 1998)
The complete DNA sequence (7876 nucleotides) of strawberry vein banding virus (SVBV) has been determined. Seven open reading frames are detected that potentially code for proteins of calculated weight 37.8; 18.3; 16.6; 56.0; 81.1; 59.0 and 12.6 kDa, respectively. Their position on the viral genome is the same as that of the corresponding proteins on the cauliflower mosaic virus (CaMV) genome. Phylogenetic analysis based on the amino acid sequence of this protein shows a closer relationship of SVBV with CaMV, figwort mosaic virus and carnation etched ring virus than with other caulimoviruses.
Keywords: DNA, Viral; ovoce; molekulární sekvence - údaje; Fruit; Open Reading Frames; otevřené čtecí rámce; sekvence nukleotidů; Base Sequence; DNA virů; Caulimovirus; Molecular Sequence Data